Social Memory from Production to Consumption; The Case of Samsun City Centre - Onur GENÇ; Tuğçe ŞANLI KATI (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
Cities have continued their existence with a dynamic process since their existence and have taken their present form. Some actors of this dynamic process have determined how cities will be shaped by creating ruptures in the historical process. The 18th century industrial revolution brought many new spaces to cities. These spaces can be classified as factory areas where various production processes take place, worker housing and transport structures that will serve factory areas. Factory areas are planned with functional location selection within the city and integrated with transportation. For this reason, they are located in city centre locations. Over time, with the changing urbanisation patterns and the expansion of the city and the change of urbanisation dynamics with new urbanisation paradigms, these factory areas have become dysfunctional over time by being squeezed as large land uses in the central locations of the cities. This study examines the transformation processes of industrial heritage areas located in Samsun city centre and the effects of these areas on social memory.